Silicon Nitride Based Non-Volatile Memory Structures with Embedded Si or Ge Nanocrystals - Horvath, Zsolt J.; Basa, P.; Jaszi, T.; Pap, A. E.; Molnar, Gy.; Kovalev, A. I.; Wainstein, D. L.; Gerlai, T.; Turmezei, P. (Communications - Scientific letters of the University of Zilina, 2010)
Memory structures with an embedded sheet of separated Si or Ge nanocrystals were prepared by low pressure chemical vapour deposition using a Si3N4 control and SiO2 tunnel layers. It was obtained that a properly located layer of semiconductor nanocrystals can improve both the charging and retention behaviour of the MNOS structures simultaneously. Memory window width of above 6 V and retention time of 272 years was achieved for charging pulses of 15 V, 10 ms.